2016
DOI: 10.1002/slct.201601536
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Natural Product (+)‐trans‐Dihydronarciclasine via an Asymmetric Organocatalytic [3+3]‐Cycloaddition and discovery of its potent anti‐Zika Virus (ZIKV) Activity

Abstract: An asymmetric total synthesis of the natural product (+)-transdihydronarciclasine has been achieved from a-azidoacetone and cinnamaldehyde precursors via a stepwise asymmetric [3 + 3]-organocatalytic cascade. The anti-Zika virus activity of this compound is also reported for the first time.Amaryllidaceae plants [1][2] continue to be a valuable source of compounds that exhibit potent anticancer, antiviral and other biological properties. As a class, the compounds feature complex, densely functionalized and synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 52 publications
0
26
1
Order By: Relevance
“…Our analyses of a panel of viruses were stimulated by our prior report indicating the potency of R430 against VZV 18 , and our recent discovery that OR430, a derivative of R430, is efficacious against ZIKV 20 . Consistent with the earlier reports, we found that R430 exerts antiviral activity against RNA viruses like ZIKV (Brazilian and Cambodian strains).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses of a panel of viruses were stimulated by our prior report indicating the potency of R430 against VZV 18 , and our recent discovery that OR430, a derivative of R430, is efficacious against ZIKV 20 . Consistent with the earlier reports, we found that R430 exerts antiviral activity against RNA viruses like ZIKV (Brazilian and Cambodian strains).…”
Section: Discussionmentioning
confidence: 99%
“…R430 also inhibited varicella zoster virus (VZV) lytic infection more potently than ACV 18 . A hydroxy analogue of R430 was recently reported to have potent activity to the Zika virus (ZIKV) 20 , suggesting that R430 and its derivatives could inhibit a spectrum of DNA and RNA viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, considering that many of isoquinolin‐1( 2H )‐one derivatives possess various antiviral activities [16e,f] and plant virus diseases are the second largest plant diseases which have caused great damage to agricultural industry, the anti‐tobacco mosaic virus (TMV) activities of part of the desired molecules were measured (Table 4). From the biological assay results in Table 4, in comparison with 1 a , their antiviral activity was significantly improved.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, strong antiviral activities of some phenanthridone alkaloids including compounds 4, 6, and 7 were reported by Gabrielsen and coworkers [33,34]. Very recently, trans-dihydronarciclasine, pancratistatin, and narciclasine have also been found to be active against Zika virus [35].…”
Section: Introductionmentioning
confidence: 87%